2017
DOI: 10.1177/1088357617735814
|View full text |Cite
|
Sign up to set email alerts
|

Training Peer Models to Promote Social Skills: Considerations for Practice

Abstract: Social skills training programs have increasingly enlisted same-age typical peers as instructors in the teaching of social skills to children with high-functioning autism spectrum disorder (ASD). The inclusion of peers in the teaching process has been found to be a critical component in these programs. Despite strong support for incorporating peers in social skills programs, there are few guidelines for training peers. The present study examined a treatment package to teach typical school-aged children skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The development of social skills is influenced by support from the surrounding environment such as family (Leano, 2015) and peers (Rodda & Estes, 2018). For students with special needs, peers are an important element because they can be a place for social learning (Mathews et al, 2018). Interaction with peers can help individuals with special needs in developing social skills that are difficult to obtain in a non-authoritarian atmosphere (Shaffer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The development of social skills is influenced by support from the surrounding environment such as family (Leano, 2015) and peers (Rodda & Estes, 2018). For students with special needs, peers are an important element because they can be a place for social learning (Mathews et al, 2018). Interaction with peers can help individuals with special needs in developing social skills that are difficult to obtain in a non-authoritarian atmosphere (Shaffer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the greatest challenges of Autism Spectrum Disorder (ASD), the varied degrees of social communicative competencies of children on the spectrum has been studied extensively (Bellini, Peters, Benner, & Hopf, 2007;Goldstein, Kaczmarek, Pennington & Shafer, 1992;Mathews, Vatland, Lugo, Koenig & Gilroy, 2018;McEvoy, et al,1988;Prendeville, Prelock & Unwin, 2006). Due to the lack of or limited communication and social skills, children with ASD have difficulty initiating, responding to, and maintaining relationships with their typically developing peers as demonstrated in their play behaviors (Prendeville, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among many interventions including peers, peer-mediated interventions are reported to be effectively employed in increasing the social interaction of children on the autism spectrum with their typically developing peers (DiSalvo & Oswald, 2002;Mathews, et al, 2018) in inclusive education settings (Goldstein, et al, 1992;Rogers, 2000). These interventions included peers as social-partners with diverse roles assigned across studies, and peer-training as the main component of the intervention (Mathews, et al, 2018). The variations reported in the planning and the implementation of peer-training including type, duration, skills taught, the nature of assigned roles, expectations of and from the peers make this component the most critical variable that directly impacts the outcome of the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure in maintaining the behavior is mostly due to the context that is highly controlled and dominated by adults (such as teachers, parents, and other professionals). [4] performed the research to increase the social skills of children with autism by using social skills training programs. The result of research showed that there is an increase in the verbal interaction of children with autism.…”
Section: Introductionmentioning
confidence: 99%